Primary care nurses' preparedness for COVID-19 in the Western Cape province, South Africa - Talitha Crowley; Danine Kitshoff; Frances de Lange-Cloete; Justine Baron; Santel de Lange; Cornelle Young; Tonya Esterhuizen; Ian Couper (AOSIS, 2021)
Introduction: The novel coronavirus 2019 or COVID-19 pandemic has brought about a global public health crisis. Primary care (PC) nurses render first line care, or refer for more specialised services. Aim: To investigate the preparedness of PC nurses for COVID-19 in the Western Cape. Setting: The Western Cape province of South Africa. Methods: We administered an online survey, with closed and open-ended questions, to 83 Stellenbosch University postgraduate PC nursing students and alumni working in the Western Cape, between 03 July and 01 September 2020. Results: The results indicated that 43.3% of participants were confident about the infection, prevention, and control (IPC) training they received and 56.7% felt prepared to provide direct care to suspected cases of COVID-19. Primary care nurses were more comfortable to triage (78.3%) than to manage persons with COVID-19 (42.2%), indicating that they may not be functioning to the full capacity of their education and training. Adequate infrastructure was reported by less than a third of the participants (30.1%) and 59.1% reported that personal protective equipment (PPE) was always available. Primary care nurses needed support in coping with stress (57.8%) although few (14.5%) reported access to mental health services. Conclusion: Primary care nurses were not prepared optimally for the COVID-19 pandemic. Challenges included adequate training, infrastructure, the availability of personal protective equipment, COVID-19 testing of health care workers and management support. Primary care nurses need comprehensive support to manage stress and anxiety.